2020
DOI: 10.1111/mec.15434
|View full text |Cite
|
Sign up to set email alerts
|

Supervised machine learning is superior to indicator value inference in monitoring the environmental impacts of salmon aquaculture using eDNA metabarcodes

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 98 publications
(179 reference statements)
5
60
0
Order By: Relevance
“…Recent studies have argued for differences in ecological function between bacteria and microbial eukaryotes in lake ecosystems [42,89,90]. More specifically, it has been argued that bacteria are more responsive to environmental changes than eukaryotes [14,18,20,42]. This is supported by our result that bacteria that are multi-task bioindicators can be indicative of more lake parameters than eukaryotic multi-task bioindicators (see figure 3).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Recent studies have argued for differences in ecological function between bacteria and microbial eukaryotes in lake ecosystems [42,89,90]. More specifically, it has been argued that bacteria are more responsive to environmental changes than eukaryotes [14,18,20,42]. This is supported by our result that bacteria that are multi-task bioindicators can be indicative of more lake parameters than eukaryotic multi-task bioindicators (see figure 3).…”
Section: Discussionsupporting
confidence: 79%
“…This is the case since organisms will only emerge as indicative for parameters they react to directly (because of their ecological niche) or indirectly (since they interact closely with organisms that are, in turn, reactive to changes in the respective parameter). Due to their functional diversity, high growth rates, large population sizes, and high surface-to-volume ratio, bacteria and microeukaryotes are very responsive to environmental changes and represent optimal bioindicators [14,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictions obtained from metazoan-assigned OTUs had kappa values between 0.211 and 0.569, whereas the SML models had kappa values raging from 0.755 to 0.881. Following on from this study, Frühe et al (2020) [92] compared the performance of SML with standard IndVal approach for prediction of environmental status. The indicator species approach directly from OTUs/ASVs has appeal due to there not being a need to assign taxonomy to the OTUs/ASVs like in the metazoan-assigned OTUs approach.…”
Section: Optimizing Model Construction and Evaluationmentioning
confidence: 99%
“…Morphological approaches, however, are often time-consuming, expensive, and require a high level of taxonomic expertise that is shrinking globally ( Jones, 2008 ). These limitations have led to numerous metabarcoding investigations describing the ecological responses of a wide range of organisms associated with enrichment states, including bacteria ( Fodelianakis et al, 2015 ; Dowle et al, 2015 ; Verhoeven et al, 2018 ; Stoeck et al, 2018a ), foraminifera ( He et al, 2010 ; Pawlowski et al, 2014 , 2016a ; Pochon et al, 2015 ), ciliates ( Stoeck et al, 2018b ), metazoans ( Lejzerowicz et al, 2015 ), or a combination of multi-trophic taxa ( Keeley, Wood & Pochon, 2018 ; Frühe et al, 2020 ). Although all of these studies have revealed consistent organismal responses to fish farm enrichment, indicating that metabarcoding is a cost-effective tool for routine monitoring, they have all used different sediment collection methods, varying amounts of starting material (from 0.25 g to 10 g of sediment), and a variety of DNA extraction kits.…”
Section: Introductionmentioning
confidence: 99%